Prognostic value of computed tomography scan detection of cartilage invasion in advanced laryngeal cancer treated with primary total laryngectomy. Issue 10 (8th July 2022) - Lee, Maxwell Y.; Lee, Jonathan; Stock, Sarah; Belfiglio, Mario; Matia, Brian; Koyfman, Shlomo; Joshi, Nikhil P.; Burkey, Brian B.; Lamarre, Eric; Prendes, Brandon; Scharpf, Joseph; Lorenz, Robert R.; et al.
Abstract: Background: We sought to determine whether detection of cartilage invasion (CI) by computed tomography predicts oncologic outcomes after primary total laryngectomy. Methods: Retrospective cohort study comparing oncologic outcomes between radiologic versus pathologic diagnosis. Results: Assessment of clear CI versus gestalt CI resulted in 84% versus 48% specificity, 90.9% versus 80.3% positive predictive value (PPV), 60.6% versus 80.3% sensitivity, 44.7% versus 48% negative predictive value (NPV), respectively. Disease‐free survival (DFS) was similar between cT4a and cT3/cT2 patients ( p = 0.87). DFS trended towards superiority among pT3/pT2 versus pT4a patients ( p = 0.18). DFS was similar among patients with CI on radiologist gestalt versus no CI ( p = 0.94). Histologically confirmed CI was associated with a hazard ratio (HR) of 1.46 ( p = 0.27), gestalt CI 1.13 ( p = 0.70), and clear CI 1.61 ( p = 0.10) for DFS. Conclusion: Gestalt determination of CI results in high sensitivity but low specificity, while clear determination of CI results in moderate sensitivity and high specificity.